Measuring Merdeka Belajar Correlativity with the National Education System Act No. 20 of 2003 and Pancasila - Franciscus Xaverius Wartoyo (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
Merdeka Belajar in the perspective of the Law No. 20 of 2003 on the National Education System, has an important role in the development of the character of the pupils. As the concept of independent university learning with a concept of hybrid education for the first three semesters in the major is in demand as part of character formation in the field. Like working on a village project, social welfare, entrepreneurship, internships in companies and so on. The national educational system within the boundaries of character education is expected to produce qualified people, in building the cultural character of the nation, the educational environment should lead to the creation of a conducive environment in accordance with the Pancasila State and UUD 1945. This research is a study with a normative jurisprudential approach. The results of this study show that character is a good objectivity over human qualities.   Keywords: Merdeka Belajar, Character Education, Law of the State, UUD 1945